2023
DOI: 10.3389/fevo.2022.1062612
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial spawning substrates to support lacustrine fish recruitment and fisheries enhancement in a Chinese lake

Abstract: Lake littoral zones with abundant submerged vegetation are considered to harbor diverse biotic communities and additionally serve as spawning grounds for important fishery resources. In recent decades, due to various human activities submerged vegetation in lakes have declined dramatically resulting in the function loss of spawning grounds. In order to enhance the recruitment of lacustrine fish (mainly Carassius auratus and Cyprinus carpio) and the proliferation of fishery resources, we explored a method of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…We have demonstrated that habitat enhancement can partially compensate the predatory effect of fish, but that it can also alter water quality and key ecosystem functions. Ecosystem-based management is promising (Feng et al, 2023;Radinger et al, 2023), but remains complex to implement, particularly in the choice of materials used to ensure a sustainable and beneficial outcome (Cooke et al, 2023). The effects of habitat enhancement occur over the longterm whereas the effects of stocking may occur in the short term, indicating that the impacts of stocking with non-native predators are difficult to reverse, despite investment in habitat enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that habitat enhancement can partially compensate the predatory effect of fish, but that it can also alter water quality and key ecosystem functions. Ecosystem-based management is promising (Feng et al, 2023;Radinger et al, 2023), but remains complex to implement, particularly in the choice of materials used to ensure a sustainable and beneficial outcome (Cooke et al, 2023). The effects of habitat enhancement occur over the longterm whereas the effects of stocking may occur in the short term, indicating that the impacts of stocking with non-native predators are difficult to reverse, despite investment in habitat enhancement.…”
Section: Discussionmentioning
confidence: 99%